PEMBELAJARAN CERITA UNTUK ANAK USIA DINI: SUATU PENDEKATAN KONTEKSTUAL BERBASIS CINTA LINGKUNGAN - Heru Kurniawan (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2012)
Abstract : Learning the story means the active action, interactive, and creative among (young) students with teachers in understanding the story as a medium of instruction, the stories read or recited by teachers for students. This confirms that the story as a learning medium used to establish interaction between pupils with the teacher, so that the active and creative interaction, children can gain knowledge related to an increase in intellectual, affective, psychomotor, linguistic, and social sensitivity of students. Creating the next generation of human beings who have a love for nature and the environment are important, one way that can be taken is to create contextual language learning that prioritizes the side effect of implanting the love to the environment since childhood. Key Words: Learning, Story, The Environment.